A Perplexing Case of Child Abuse. Issue 8 (August 2015) - Starr, Michelle; Klein, Eileen J.; Sugar, Naomi
<x xml:space="preserve">Abstract</x> Abstract The following case presents a pediatric patient with an oral foreign body secondary to intentional injury. This patient had presented several previous times for medical care, first with thigh bruises, then mouth bleeding, and finally with the unusual finding of a sharp foreign body embedded in the tongue. This case illustrates the importance of considering physical abuse in the differential of orofacial injuries. Frenulum tears, both in mobile and nonmobile children, are concerning for abuse and should trigger further evaluation. This case highlights the complexity of assessing for physical abuse when examining a patient. Bruising, as seen in this patient, is common in children, and the clinical team must determine if the pattern, location, and history are concerning for a nonaccidental injury. Physicians should strongly consider child abuse in the emergency department when patients present with concerning physical examination findings such as bruises or orofacial injures without corroborating history. Finally, this case reviews mandatory reporting requirements for physicians and other medical professionals and highlights the obligation to report suspected child abuse even when not working in the professional capacity at the time of recognition.